Characterization of Particle Size Distribution of Plasma Lipoproteins in Dairy Cattle Using High-Resolution Polyacrylamide Electrophoresis - Duran, Marcos Jofree; Kannampuzha-Francis, Jasmine; Nydam, Daryl; Behling-Kelly, Erica (Frontiers in Animal Science, 2021)
Plasma lipoproteins play critical roles in energy metabolism and inflammation. Concentrations of high density lipoproteins (HDL) have been linked to reproductive outcomes and milk yields in dairy cattle. Low-density lipoproteins (LDL), which are enzymatically formed in the blood from very low density lipoproteins (VLDL) following secretion by the liver, have been used as a surrogate marker of liver function due to the rapid influx of circulating VLDL into the lactating mammary gland. In humans, the composition of plasma lipoproteins is reflected in lipoprotein particle size distribution, and both of these parameters are highly predictive of disease development and related health outcomes. Bovine HDL are overall larger, less dense particles compared to human HDL. Lipoprotein particle size distribution in both health and disease is understudied in the bovine. We hypothesize that a more detailed analysis of lipoproteins could hold diagnostic and/or prognostic value in the study of dairy cattle health and production. In this study, we took the first steps in this characterization and used a high resolution polyacrylamide gel electrophoretic assay to better define LDL and HDL at the subfraction level in Holstein cows at different stages of lactation. We extensively characterized the lipoprotein particle size distribution in healthy lactating dairy cattle. We identified subfractions of LDL that were evident only in the dry period and subfractions of HDL that were highest in cows during mid-lactation. Use of this method could be informative in the study of multiple herds and management strategies, including longitudinal evaluation of animals and production parameters.